Return to Ibn Khaldun—Again. Issue 1 (February 2015) - Dale, Stephen Frederic
Abstract : These three books, written by sociologist Syed Farid Alatas and historian Allen James Fromherz, represent the continued academic fascination with the Muqaddimah, the work of the North African Arab Muslim historical theorist Ibn Khaldun (1332–1406). The Muqaddimah has been the subject of an entire library of articles and books since it was first published and translated in Europe in the mid-nineteenth century. Written mainly by Westerners and Western-educated Middle Easterners, most of these publications have studied one or another aspect of Ibn Khaldun's dialectical model of tribal state formation, which constitutes the intellectual core of the Muqaddimah. Many authors of these works have also noticed and commented on the similarity of Ibn Khaldun's historical model to Western sociological theory. Relatively few scholars have written about Ibn Khaldun himself. Most but not all of these scholars agree that Ibn Khaldun was a brilliantly original intellectual, but many express different views about the genesis and nature of his ideas and their significance. Alatas and Fromherz provide two contrasting studies. Alatas's two books are closely related sequential studies, devoted to explaining Ibn Khaldun's model and relating it to the social sciences. Fromherz's work is biographical, although he also discusses Ibn Khaldun's theories. Both authors make significant contributions to the understanding of the man and his ideas, while also implicitly demonstrating why Ibn Khaldun and the Muqaddimah will continue to be subjects of research and controversy.